2020
DOI: 10.1643/cp-19-265
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil: Lymphocyte Ratios as a Measure of Chronic Stress in Populations of the Hellbender (Cryptobranchus alleganiensis) across a Habitat Quality Gradient

Abstract: Amphibians are currently facing widespread population declines, primarily due to the introduction of anthropogenic stressors, which have the potential to alter ecosystem dynamics and elicit long-term physiological responses resulting in overall population declines. Population assessments typically rely upon genomics, demography, and geographic isolation; however, when physiological parameters are included, mechanistic explanations for population declines can be determined. Rapid population assessments that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(90 reference statements)
1
1
1
Order By: Relevance
“…While we did not evaluate correlations between N:L ratios and water quality directly, WsRp forest is positively correlated with water quality in our system ( Supplementary Figure S1 ). Thus, the lack of a negative association between WsRp forest and WBC PC1 in our study contrasts somewhat with findings of Litmer et al (2020) , who reported an increase in hellbender N:L ratios in response to degraded water quality. One possible explanation for this contrast could be that parasite effects simply overwhelmed any effects of altered abiotic habitat conditions in our systems.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…While we did not evaluate correlations between N:L ratios and water quality directly, WsRp forest is positively correlated with water quality in our system ( Supplementary Figure S1 ). Thus, the lack of a negative association between WsRp forest and WBC PC1 in our study contrasts somewhat with findings of Litmer et al (2020) , who reported an increase in hellbender N:L ratios in response to degraded water quality. One possible explanation for this contrast could be that parasite effects simply overwhelmed any effects of altered abiotic habitat conditions in our systems.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, we found that N:L ratios and eosinophils were often co-elevated, which is indicative of parasitic infection ( Hopkins et al , 2016 ), while a typical response to glucocorticoid secretion is characterized by increasing N:L ratios but a decline in eosinophils ( Davis et al , 2008 ; Falso et al , 2015 ). Otherwise, mean monthly N:L ratios observed in our study between April and August (range: 0.28–0.66; Supplementary Table S1 ) were similar to those reported for most sites sampled by Litmer et al (2020) , which only rarely exceeded 1.0, and thus collectively suggest that few if any of the sub-populations sampled in either study exhibited signals of true physiological stress (i.e. N:L ratio > 1.0; Davis and Maerz, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…Pre-slaughter stress can affect postmortem muscle metabolism and meat quality, leading to increased levels of catecholamines and creatinine kinase in the body, rapid glycolysis, and lactic acid buildup in the meat (Bourguet et al, 2011;Pisestyani et al, 2015). Animal stress levels can be measured using neutrophil-lymphocyte ratio (Litmer et al, 2020). Previous studies have shown that pigs executed with electrical stunning had a lower ratio, and this condition showed reduced stress (Anugrah et al, 2022), further supported by a decrease in superoxide dismutase level (Prayoga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%